Organ Donation in an African Culture - Kunle, Ayinde Jamiu (Bangladesh Journal of Bioethics, 2019)
This paper is an attempt to examine the traditional Yoruba beliefs about organ donation. Organ donation and transplantation remain a rare occurrence in African, this to a large extent can be as a result of the traditional African orientation on the one hand and the advancement in medical research that come with transplanting organ on the other. In this paper, we x-ray the problem of organ shortage in most African countries. We identified that apart from lack of awareness on organ donation, Africans traditionally would not be willing to donate their organs after death. This paper critically examines beliefs in some African cultures and their relationship with organ donation. We analyze life after death in the Yoruba tradition and the belief in the continuation of the body after death. The paper concludes that the African belief in the continuation of the body in the afterlife contributes to the non-willingness of Africans to donate an organ after death.